2017
DOI: 10.3389/fped.2017.00051
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Hypertension in Children and Adolescents: Methodology and Current Practice Recommendations

Abstract: Hypertension (HTN) requires urgent, uniform, and consistent attention across all frontiers of pediatric health care not only because of established links between the onset of HTN during one’s youth and its sustenance throughout adulthood but also because of the sequelae associated with the disease’s trajectory, such as cardiovascular disease, end organ damage, and decreased quality of life. Although national guidelines for the diagnosis and management of pediatric HTN have been available for nearly 40 years, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…Hypertension still becomes the world’s concern as this disease could occur at such a young age with its continuous risks until adult and contribute to heart disease, organs damage, and decreased quality of life [1], [2]. Early management of hypertension could decrease mortality and morbidity related to this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension still becomes the world’s concern as this disease could occur at such a young age with its continuous risks until adult and contribute to heart disease, organs damage, and decreased quality of life [1], [2]. Early management of hypertension could decrease mortality and morbidity related to this disease.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Meng L et al showed the increased blood pressure percentage in children aged 3 – 18 years as 3.1% [3]. Also reported that between 2011 to 2014, the prevalence of children hypertension aged 8 – 17 years old was 2.2% [2]. A study by Gupta et al found the aetiology of hypertension itself, of which 423 children aged > 5 years who had hypertension were 275 children (65%) with essential hypertension of 43% and secondary by 57%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, repeating AOBP measurements only in those identified with high BP during initial measurements saves time and has been recommended for adolescents 23 . It has been reported that more than 90% of adolescents aged 13 -18 years participating in the US National Health and Nutrition Examination Survey (NHANES) had their BP classification remaining the same in follow up measurements and <3% had an increase in BP classification 23,24 . Similarly, in this study, all participants with normal BP using the first method (63.4%) remained in the same BP classification during subsequent (second and third) BP measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, more than 90% of study participants never had their BP measured before the day of enrollment; a number we feel is representative of the general population of adolescents in Tanzania and sub-Saharan Africa at large where existing adolescent health programs have traditionally focused on sexual and reproductive health 12 . In addition, repeating AOBP measurements only in those identified with high BP during initial measurements saves time and has been recommended for adolescents 23 . It has been reported that more than 90% of adolescents aged 13 -18 years participating in the US National Health and Nutrition Examination Survey (NHANES) had their BP classification remaining the same in follow up measurements and <3% had an increase in BP classification 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…As poucas publicações sobre o consumo de alimentos fora do lar em adolescentes brasileiros limitam-se a descrever as frequências de consumo nessa população e a contribuição da alimentação fora de casa para o consumo de itens específicos 9 . Não há estudos que tenham investigado a associação entre consumo de alimentos fora de casa e marcadores bioquímicos de doenças crônicas na população brasileira, apesar de já se saber que altos níveis de biomarcadores para essas doenças na adolescência estão associados a uma maior chance de desenvolvimentos das DCNT na vida adulta 10,11 .…”
Section: Introductionunclassified